2013
DOI: 10.1159/000354381
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Segment Optical Coherence Tomography for Imaging the Sub-Tenon Space

Abstract: In this study, we report the ability of anterior segment optical coherence tomography (AS OCT) in imaging the sub-Tenon space and its clinical application. High-speed AS OCT (Carl Zeiss Meditec, Dublin, Calif., USA) was used to visualize the sub-Tenon space during sub-Tenon injection. The sub-Tenon spaces, Tenon thickness, conjunctiva-Tenon thickness, injecting cannula position in relation to the sub-Tenon space and drug localization/distribution in the sub-Tenon space were analyzed. The sub-Tenon spaces of 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…The mean thickness of the anterior Tenon's capsule in this previous study was 0.21 6 0.07 mm. In Figure 2 of the Kumar et al 5 study, Tenon's capsule showed a similar reflectance with splitting fibers similar to the findings for the Tenon's capsule in the posterior segment in our current study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The mean thickness of the anterior Tenon's capsule in this previous study was 0.21 6 0.07 mm. In Figure 2 of the Kumar et al 5 study, Tenon's capsule showed a similar reflectance with splitting fibers similar to the findings for the Tenon's capsule in the posterior segment in our current study.…”
Section: Discussionsupporting
confidence: 91%
“…2A, 2C, 2E). Using highspeed anterior segment OCT, Kumar et al 5 examined the anterior Tenon's capsule in 12 eyes which received a drug injection into the posterior sub-Tenon space for the therapy of uveitis. The mean thickness of the anterior Tenon's capsule in this previous study was 0.21 6 0.07 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, higher CP concentration at the delivery site could be obtained via SMS due to slower clearance rate. It has been shown that the vascular density is low in sub-Tenon’s area, 33 which can decrease drug clearance by blood flow. Furthermore, the concentration gradient can enhance drug penetration from the scleral surface to the retina/vitreous.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, higher CP concentration at the delivery site could be obtained via SMS due to slower clearance rate. It has been shown that the vascular density is low in sub-Tenon's area, 33 which can decrease drug clearance by blood flow. Furthermore, the concentration gradient can enhance drug penetration from the scleral surface to the retina/vitreous.- [34][35][36] Thus, the longer period for CP loading at the injection site, the higher possibility for CP penetrating into the sclera and getting to the ocular tissue.…”
Section: Discussionmentioning
confidence: 99%
“…TC has a dense amorphous histological structure and contains broblasts [13][14][15][16][17]. Being one connective tissue, TC heals completely by brosis, [7,14,19,20] compromising its mobility and providing poor TRAB outcomes. Furthermore, the TC adheres only weakly to the episclera, and is separated from it by the STS [20].…”
Section: Introductionmentioning
confidence: 99%